Development of the Problem of Health Education of Secondary Schools Students in Poland in the Research of Polish Scientists after 1989 - Larysa Slyvka (Vasyl Stefanyk Precarpathian National University, 2022)
The article analyzes some historical and pedagogical works of Polish scholars on the formation and development of health education for students of Polish secondary schools, written after 1989. The study is based on the chronological-subject principle of historiographical analysis of sources. The opinion is expressed that the research of scientists of the analyzed period clearly shows a systematic and consistent interest in reflections on solving the problem of health care through education and upbringing. The names of historical and pedagogical investigations, the authors of which are announced Vanda Bobrovska-Novak (pol. Wanda Bobrowska-Nowak), Aneta Boldyriev (pol. Aneta Bołdyrew), Ryshard Vashtyl (pol. Ryszard Wasztyl), Elzhbieta Vientskovska (pol. Elżbieta Więckowska), Barbara Voinarovska (pol. Barbara Woynarowska), Matsiei Demel (pol. Maciej Demel), Zbihnei Domoslavskyi (pol. Zbigniew Domosławski), Kazymyr Drahanskyi (pol. Kazimierz Dragański), Bozhena Zavadska (pol. Bożena Zawadzka), Teresa Zolkovska (pol. Teresa Ziołkowska), Eva Elzhbieta Kalamatska (pol. Ewa Elżbieta Kałamacka), Barbara Luchynska (pol. Barbara Łuczyńska), Yoanna Maikhzhyk-Mikula (pol. Joanna Majchrzyk-Mikuła), Barbara Morashevska (pol. Barbara Moraczewska), Monika Navrot-Borovska (pol. Monika Nawrot-Borowska), Valdemar Nadolskyi (pol. Waldemar Nadolski), Barbara Niedzhvidzka (pol. Barbara Niedźwidzka), Yan Nosko (pol. Jan Nosko), Mahdalena Patsorek (pol. Paciorek Magdalena), Barbara Pendrashevska-Soltys (pol. Barbara Pędraszewska-Sołtys), Malhozhata Poslushna (pol. Małgorzata Posłuszna), Bohdan Rok (pol. Bogdan Rok), Potr Slavinskyi (pol. Piotr Sławiński), Yoanna Torovska (pol. Joanna Torowska), Bozhena Urbanek (pol. Bożena Urbanek), Andzhei Felkhner (pol. Andrzej Felchner), Mahdalena Florek-Lushchki (pol. Magdalena Florek-Łuszczki), Potr Stanislav Franashek (pol. Piotr Stanisław Franaszek), Anna Tsishinska (pol. Anna Cisińska), Marchin Sherlie (pol. Marcin Szerle), Anna Shyliar (pol. Anna Szylar), Leonard Shymanskyi (pol. Leonard Szymański), Beata Shchepanska (pol. Beata Szczepańska), Zyhmunt Yavorskyi (pol. Zygmunt Jaworski), Ivona Yanitska (pol. Iwona Janicka), etc. It is concluded that Polish scholars of the "modern" historiographical period systematically consider rather long periods (centuries or even more) of health-preserving education of secondary school students, turning to the philosophical principles of consideration and interpretation of pedagogical realities. trace the general tendencies of the specified pedagogical process, allocate cyclic, linear, spiral, stage, civilizational and paradigmatic character of its development.